NUTRITIONAL STATUS OF BAROMA RICE IN DIFFERENT COOKING METHODS - Akmalia, Hafidha Asni; Febriana, Asri; Pranatami, Dwimei Ayudewandari; Adawiyah, Putri Rabiatul (Jurnal Gizi dan Pangan Soedirman, 2024)
Rice is one of the staple foods which is the main source nutrition such as carbohydrates, vitamins, minerals, protein, fat and fiber. The various rice cultivars that have been developed have different nutritional variations so that they provide choices according to the wishes of the community. This study aims to compare the profile of the compound content of Baroma rice in different cooking methods. Baroma rice was chosen in the study because the test for the content of compounds had never been carried out considering that the rice cultivar is a new type. The nutrients such as total protein, total fat, total sugar, starch, and calories were measured in the cooking method using stove and magic com with a completely randomized design and repeated 3 times. The results were analyzed using unpaired t-test analysis for the effect of different cooking methods. The result showed that magic com cooking increases fat and protein content while stove cooking elevates calories, starch, and total sugar.